Die Trauermücken in Deutschland - ökosystemare Bedeutung, zönozoologische Koinzidenzen und bioindikatorisches Potential (Diptera: Sciaridae). - Menzel, Frank; Schulz, Ulrich (Contributions to Entomology = Beiträge zur Entomologie, 2007)
Black Fungus Gnats (Sciaridae), with more than 400 species recorded in Germany, contribute significantly to biodiversity of Diptera in natural and man-made landscapes. Their importance for the ecosystem is a result of the phytosaprophagous habits of the larvae, their function in the process of decomposition, and their frequent occurrence at high densities, in almost all types of soil. After the description of their contribution to biodiversity and the services which they render to the ecosystem, an overview of the number of species in different German biotopes is given. This synopsis is based on all published data on population densities, biomass and distribution of Sciarid flies in Germany. For the first time a survey is presented of Sciarid biodiversity and community structure (coincidences of dominant species) in different habitats. Based on this, the suitability of Sciaridae as bio-indicators is discussed. Keywords Diptera, Nematocera, Sciaridae, Germany, biodiversity, distribution, ecology, soil dwelling larvae, ecosystem services, community structure, bio-indicators.